2020
DOI: 10.1080/22221751.2020.1730247
|View full text |Cite
|
Sign up to set email alerts
|

Evidence that the second human pegivirus (HPgV-2) is primarily a lymphotropic virus and can replicate independent of HCV replication

Abstract: Tang (2020) Evidence that the second human pegivirus (HPgV-2) is primarily a lymphotropic virus and can replicate independent of HCV replication, Emerging Microbes & Infections, 9:1,[485][486][487][488][489][490][491][492][493][494][495] ABSTRACT The second human pegivirus HPgV-2 is a novel blood-borne virus that is strongly associated with the hepatitis C virus (HCV) infection. However, the molecular evidence for their association as well as the natural history and tissue tropism of HPgV-2 remain to be e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 49 publications
1
5
0
Order By: Relevance
“…These results suggest that HPgV-2 per se does not stimulate strong innate immune response to pose high selection pressure upon HPgV-2 infection. Our results are in line with our previous findings that HPgV-2 infection results in limited or absence of pathogenicity (Wang et al, 2018b;Sridhar et al, 2019) and is at least not associated with viral hepatitis although it always coinfects with HCV (Wang et al, 2018b;Wan et al, 2020). Therefore, for HPgV-2/HCV-coinfected subjects, even though HPgV-2 confronts strong immune selective pressure, the immune responses may be mainly induced by HCV while the specific immune response against HPgV-2 may be moderate, which is in accordance with the decreased pro-inflammatory cytokines expression after HCV elimination (Figure 4A).…”
Section: Discussionsupporting
confidence: 93%
“…These results suggest that HPgV-2 per se does not stimulate strong innate immune response to pose high selection pressure upon HPgV-2 infection. Our results are in line with our previous findings that HPgV-2 infection results in limited or absence of pathogenicity (Wang et al, 2018b;Sridhar et al, 2019) and is at least not associated with viral hepatitis although it always coinfects with HCV (Wang et al, 2018b;Wan et al, 2020). Therefore, for HPgV-2/HCV-coinfected subjects, even though HPgV-2 confronts strong immune selective pressure, the immune responses may be mainly induced by HCV while the specific immune response against HPgV-2 may be moderate, which is in accordance with the decreased pro-inflammatory cytokines expression after HCV elimination (Figure 4A).…”
Section: Discussionsupporting
confidence: 93%
“…Our previous studies showed that sofosbuvir can inhibit HCV replication but not HPgV-2 replication ( 13 , 14 ). Sofosbuvir is a uridine analog and a nucleotide inhibitor (NI) of RdRp for the treatment of chronic HCV infection ( 21 23 ).…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, our previous studies indicated that direct-acting antiviral (DAA) treatment, such as the nucleotide inhibitor (NI) sofosbuvir targeting viral RdRp, could eliminate HCV but not HPgV-2 infection ( 13 , 14 ). The preclinical assessments and clinical analysis of sofosbuvir trials have shown that mutations in HCV RdRp lead to a decrease in drug susceptibility ( 15 18 ) and that the drug resistance is closely related to RdRp fidelity ( 19 , 20 ).…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, a recent study shows that, like HPgV-1, HPgV-2 appears to be lymphotropic. More study of this virus is needed ( 59 ). Since current knowledge related to HPgV-2 is limited, the virus is not in the same phylogenetic lineage as HPgV-1 and is not known to influence other diseases, HPgV-2 will not be discussed further in this review.…”
Section: Introductionmentioning
confidence: 99%